Functional and Logic Programming 11th International Symposium, FLOPS 2012, Kobe, Japan, May 23-25, 2012. Proceedings - Schrijvers, Tom.; Thiemann, Peter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 11th International Symposium on Functional and Logic Programming, FLOPS 2012, held in Kobe, Japan, in May 2012. The 19 research papers and 3 system demonstrations presented in this volume were carefully reviewed and selected from 39 submissions. They deal with declarative programming, including functional programming and logic programming.
Keywords: Computer science; Software engineering; Logic design; Artificial intelligence; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Mathematical Logic and Formal Languages; Artificial Intelligence (incl. Robotics).; Programming Techniques